2021
DOI: 10.1002/cmtd.202100002
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Mechanochemistry for the Synthesis of DNA on Ionic Liquid Supports

Abstract: The standard methodology for the synthesis of oligonucleotides is the solid-phase method. Here, we report the first case of mechanochemistry being directly applied to synthesising a dinucleotide on a soluble support. While mechanochemistry eliminates the need to solubilise a supported oligomer in the solution phase for phosphoramidite coupling, the support still confers the benefit of being able to purify the product by precipitation or by simple liquid-liquid extractions as needed. Furthermore, this study als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Finally, while the challenges of achieving good isolated yields following chromatography purifications still remain, we observed that conditions where nucleosides and nucleotides could be exhaustively dried offered better outcomes. We had made similar observations when handling P(III) reagents with nucleosides [ 43 , 44 ]. Yet, when we applied this synthetic approach to isotopically labeled NAD nucleoside precursors, we were able to generate an NAD isotopologue in good isolated yields; in quantities that would be well suited to inform on exogenous NAD turn-over, including NAD’s use by sirtuins, PARP enzymes, glycohydrolases, as well as reductases, in cell based-assays by mass spectrometry.…”
Section: Resultsmentioning
confidence: 82%
“…Finally, while the challenges of achieving good isolated yields following chromatography purifications still remain, we observed that conditions where nucleosides and nucleotides could be exhaustively dried offered better outcomes. We had made similar observations when handling P(III) reagents with nucleosides [ 43 , 44 ]. Yet, when we applied this synthetic approach to isotopically labeled NAD nucleoside precursors, we were able to generate an NAD isotopologue in good isolated yields; in quantities that would be well suited to inform on exogenous NAD turn-over, including NAD’s use by sirtuins, PARP enzymes, glycohydrolases, as well as reductases, in cell based-assays by mass spectrometry.…”
Section: Resultsmentioning
confidence: 82%
“…In order to reduce solvent usage, in 2021 Migaud and co-workers demonstrated the concept of using an ionic liquid support in combination with liquid-assisted mechanochemistry for various aspects of oligonucleotide synthesis (Scheme 29 ). 125…”
Section: Salient Developments In the Mechanochemical Activation Of Sy...mentioning
confidence: 99%
“…In order to overcome this issue, we turned to mechanochemistry. Protocols in which reagents are subjected to intimate mixing and grinding using ball mills have become increasingly popular in recent years, affording reaction products that cannot be obtained using traditional solution-based methods. Additionally, the use of mechanochemistry obviates the need for solvent and can give short reaction times, good scalability, and even opportunities for in situ reaction monitoring. , Mechanochemical P-centered nucleophilic substitution has been applied to build P–O­(N) bonds in small molecules and functional polymers. , …”
mentioning
confidence: 99%